A Step towards Identity Construction or Genocide? Ideological Transformations and Propaganda in the Ottoman Empire in 1911-1913 - Galustyan, Regina (ՀՀ ԳԱԱ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
This study explores two features of the Turkish nation-building process on the ideological level in the late Ottoman Empire in 1911-1913. The territory losses and population declines following the Italo-Turkish and Balkan Wars and the ensuing influx of Muslim refugees from the Balkans created a favorable environment for the Turkish government to coordinate and produce the propaganda of Turkism en-masse within the multi-ethnic Ottoman Empire. The period of 1911-1913 stands as a crucial phase in the top-down nationalization of the Ottoman masses, which later would have a great impact on the developments in the country before, during, and after World War I. This period was severely detrimental for the indigenous Christian communities of the Ottoman Empire. Thus, two particular aspects of the construction of a “Turkish” identity through the usage of state propaganda are stressed in the article: the construction of an “other” and the glorification of a common Turkish past. Both largely determined Turkish self-perception during the era and defined the code of action against non-Turkish elements of the Empire.
Keywords: History; Genocide; Ottoman Empire